Does amantadine induce acute psychosis? A case report and literature review - xu W; Wei N; Xu Y; Hu S (Neuropsychiatric Disease and Treatment)
Wei-juan Xu,1,2 Ning Wei,1,2 Yi Xu,1,2 Shao-hua Hu1,2 1Department of Psychiatry, The First Affiliated Hospital of Zhejiang University School of Medicine, 2The Key Laboratory of Mental Disorder’s Management of Zhejiang Province, Hangzhou, People’s Republic of China Background: Over-the-counter cold medicines, which contain amantadine, are widely used in the People’s Republic of China. Clinicians are familiar with the psychosis caused by long-term treatment with amantadine, especially in elderly patients; however, early-onset psychotic complications among healthy young individuals have rarely been reported. Case presentation: This article reports the case of a 28-year-old patient who presented with hallucination–delusion syndrome soon after treatment with cold medicine containing amantadine hydrochloride and acetaminophen. The symptoms resolved completely after a 2-week course of paliperidone treatment. Conclusion: Clinicians should be sensitive to the acute psychotic complications induced by an interaction between amantadine and acetaminophen. Keywords: amantadine, acetaminophen, side effects